Laryngology A Case-Based Approach. - Sandhu, Guri S. (Plural Publishing, Incorporated, 2018)
Laryngology: A Case-Based Approach is an invaluable new text for clinicians and students covering evidence-based assessment and management of a full range of laryngological conditions. This unique text examines 55 common and rare cases and covers pediatric and adult patients. The cases are separated into four sections: pediatric, voice and airway, general/systemic, and dysphagia/swallowing.